Who receives their complex cancer surgery at low-volume hospitals? - Al-Refaie, Waddah B; Muluneh, Binyam; Zhong, Wei; Parsons, Helen M; Tuttle, Todd M; Vickers, Selwyn M; Habermann, Elizabeth B (Journal of the American College of Surgeons, 2012)
Previous literature has consistently shown worse operative outcomes at low-volume hospitals (LVH) after complex cancer surgery. Whether patient-related factors impact this association remains unknown. We hypothesize that patient-related factors contribute to receipt of complex cancer surgery at LVH. Using the 2003-2008 National Inpatient Sample, we identified 59,841 patients who underwent cancer operations for lung, esophagus, and pancreas tumors. Logistic regression models were used to examine the impact of sociodemographic factors on receipt of complex cancer surgery at LVH. Overall, 38.4% received their cancer surgery at LVH. A higher proportion of esophagectomies were performed at LVH (70.3%), followed by pancreatectomy (38.2%) and lung resection (33.8%). Patients who were non-white, with non-private insurance, and had more comorbidities were all more likely to receive their cancer surgery at LVH (for all, p < 0.05). Multivariate analyses continued to demonstrate that non-white race, insurance status, increased comorbidities, region, and nonelective admission predicted receipt of cancer surgery at LVH across all 3 procedures. In this large national study, non-white race and increased comorbidities contributed to receipt of cancer surgery at LVH. Patient selection and access to high-volume hospitals are likely reasons worthy of additional investigation. This study provides additional insight into the volume-outcomes relationship. Given the demonstrated outcomes disparity between high-volume hospitals and LVH, future policy and research should encourage mechanisms for referral of patients with cancer to high-volume hospitals for their surgical care.